Cultural Traditions in the Pottery of the Eneolithic Volga Population - Irina N. Vasilyeva (Археология евразийских степей)
The article deals with the generalization of information on pottery technology of the Volga region population in the Eneolithic period, got through technical-technological analysis. The data on 1187 vessels from 23 Eneolithic monuments (sites and burial grounds) of the Lower Volga region and the south of the Middle Volga are involved. The results of the study in 4 directions are proposed for discussion: 1) potters' ideas about the initial plastic raw materials; 2) traditions of making pottery paste; 3) ways of designing and shaping vessels; 4) methods for making products durable and waterproof. These directions are provided with information base and are important in characterizing cultural traditions in pottery. Technological data are systematized in statistical tables and confirmed by micrograph. Conclusions are drawn about the emergence of new technologies and continuity with Neolithic pottery.